Crystallization and preliminary X-ray analysis of human rhinovirus serotype 2 (HRV2). - Verdaguer, N; Marlovits, T; Bravo, J; Stuart, D; Blaas, D; Fita, I (1999)
Human rhinoviruses, the major cause of mild recurrent infections of the upper respiratory tract, are small icosahedral particles. Over 100 different serotypes have been identified. The majority (91 serotypes) use intercellular adhesion molecule 1 as the cell-attachment site; ten serotypes (the minor group) bind to members of the low-density lipoprotein receptor. Three different crystal forms of the minor-group human rhinovirus serotype 2 (HRV2) were obtained by the hanging-drop vapour-diffusion technique using ammonium sulfate and sodium/potassium phosphate as precipitants. Monoclinic crystals, space group P2(1), diffracted at least to 2.8 A resolution, and two complete virus particles were located in the crystal asymmetric unit. A second type of crystals had a compact cubic like morphology and diffracted beyond 2.5 A resolution. These crystals belong to a primitive orthorhombic space group, with unit-cell parameters a = 309.3, b = 353.5, c = 759.6 A, and contain one virus particle in the asymmetric unit. A third type of crystals, with a prismatic shape and belonging to space group I222, was also obtained under similar crystallization conditions. These latter crystals, with unit-cell parameters a = 308.7, b = 352.2, c = 380.5 A, diffracted to high resolution (beyond 1.8 A) and contained 15 protomers per asymmetric unit; this requires that three perpendicular crystal twofold axes coincide with three of the viral particle's dyad axes.